Effect of Iraqi Apricot Seed Extract on Some Physiological Parameters in Male Rats - Mohammad, Noor Sabar Khalaf; Ali, Alia Hussein; Salah, Firas Subhi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Amygdalin specifically represents the apricot (Prunus armeniaca) seed in the Rosacea family of plants. Except for cyanogenic glycoside, the seeds include a variety of substances, including trace minerals, vitamins, carbohydrates, organic acids, esters, phenols, and terpenoids. It is well known that bioregulators have the ability to control the activity of certain hormones and enzymes. The current study examined the effect of Iraqi apricot seed extract on physiological parameters in male rats, including blood parameters, hormone parameters, and antioxidant parameters, as well as histological studies of the spleen and testes. The study comprised four groups, each consisting of six animals. The animals in the control group received distilled water as their treatment. G1 received an extract (10 mg b.w.), G2 received an extract (20 mg b.w.), and G3 received an extract (40 mg b.w) orally every day for 30 days. The results showed a significant increase in WBC and blood platelets (P≤0.05), as well as T3 and T4. When compared with the control, TSH shows a significant decrease (P≤0.01) in the three groups. While FSH, LH, and testosterone hormone showed a significant decrease (P≤0.01) in the G1 and G2 groups, MPO, MDA, GPX, SOD, vitamin C, and E showed a significant decrease (P≤0.01) when compared with the control group. Finally, the histological examination showed that the spleen and testis in all groups showed a normal appearance after 30 days.